2011
DOI: 10.1016/j.actatropica.2011.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Old focus of cysticercosis in a senegalese village revisited after half a century

Abstract: The objective of this epidemiological study was to determine whether cysticercosis and especially neurocysticercosis is endemic in Soutou village about half a century after the 1962 outbreak. This study was carried out from September 2009 to February 2010. It involved a questionnaire administration, serology, treatment, coproscopy and neuro-imaging. Four hundred and three serum samples were collected from the village people, which covered 94% of the village population. By using a parallel combination of the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 16 publications
2
20
1
Order By: Relevance
“…Findings indicate detection of active cysticercosis in 16.7% of the human population while 45.3% tested positive for exposure to larval T. solium through detection of antibodies. These findings are higher in comparison to that reported elsewhere in the region such as 4.6% (Ag-ELISA), 6.9% (EITB) and 40.8% (Ab-ELISA) in Burundi [25], 12.1% (Ab-ELISA) in Mozambique [26], 0.4%–3% (Ag-ELISA) in Cameroon [27], [28], and 7.7% (Ag-ELISA and EITB) in Senegal [29], but lower than the 21.6% (Ag-ELISA) recently reported from the Democratic Republic of Congo [30].…”
Section: Discussioncontrasting
confidence: 71%
“…Findings indicate detection of active cysticercosis in 16.7% of the human population while 45.3% tested positive for exposure to larval T. solium through detection of antibodies. These findings are higher in comparison to that reported elsewhere in the region such as 4.6% (Ag-ELISA), 6.9% (EITB) and 40.8% (Ab-ELISA) in Burundi [25], 12.1% (Ab-ELISA) in Mozambique [26], 0.4%–3% (Ag-ELISA) in Cameroon [27], [28], and 7.7% (Ag-ELISA and EITB) in Senegal [29], but lower than the 21.6% (Ag-ELISA) recently reported from the Democratic Republic of Congo [30].…”
Section: Discussioncontrasting
confidence: 71%
“…tapeworm eggs or sometimes adult tapeworm segements (Lightowlers et al, 2016). Coproscopy has been used in human surveys in West Africa (Gweba et al, 2010;Secka et al, 2011).…”
Section: Diagnosis Of Taeniasismentioning
confidence: 99%
“…All three studies confirmed epilepsy by ILAE definition/physician. In Senegal, a study [42] showed that one of 10 CT-scan positives individual by Ag-ELISA and EITB was reported to have epileptic seizures, and cerebral CT-scans showed that 23.3% of the seropositive were affected by neurocysticercosis. In Togo, a previous study [57] showed that cysticercosis (confirmed by ELISA, anatomopathological examination, cranial or muscle X-ray) caused 29.5% epilepsy in sufferers.…”
Section: Discussionmentioning
confidence: 99%
“…Human taeniasis was obtained from two studies by stool microscopy [25,46] with a prevalence ranging from 8.6 to 40% among a total of 1953 individuals in the region. Human cysticercosis in Senegal was obtained from one study performing antigen and antibody ELISA [42]. The total number of individuals in the study were 403, and prevalence of both antigen and antibody was 7.6%.The prevalence of epilepsy in the country was obtained from two selected studies [52,53] and the prevalence of epilepsy ranged from 8.3/1000 to 14.2/1000 in a total of 12,182 individuals.…”
Section: Human Cysticercosis Taeniasis and Epilepsy In West Africamentioning
confidence: 99%
See 1 more Smart Citation